If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -8) = -4(3x + 7) Reorder the terms: 3(-8 + x) = -4(3x + 7) (-8 * 3 + x * 3) = -4(3x + 7) (-24 + 3x) = -4(3x + 7) Reorder the terms: -24 + 3x = -4(7 + 3x) -24 + 3x = (7 * -4 + 3x * -4) -24 + 3x = (-28 + -12x) Solving -24 + 3x = -28 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -24 + 3x + 12x = -28 + -12x + 12x Combine like terms: 3x + 12x = 15x -24 + 15x = -28 + -12x + 12x Combine like terms: -12x + 12x = 0 -24 + 15x = -28 + 0 -24 + 15x = -28 Add '24' to each side of the equation. -24 + 24 + 15x = -28 + 24 Combine like terms: -24 + 24 = 0 0 + 15x = -28 + 24 15x = -28 + 24 Combine like terms: -28 + 24 = -4 15x = -4 Divide each side by '15'. x = -0.2666666667 Simplifying x = -0.2666666667
| 38+7x=8(k+4) | | 14=3u-10 | | 8a+6=-3 | | 108-6x=30x+20 | | 5v+10=-5 | | 1.7W=3.1 | | 6-10x=30x+20 | | -5-(15y-1)=1(7y-16)-y | | -14-9x=8x+20 | | (x+3)+75*(25*6)= | | 4x+8=-6x-30 | | 3v-7=20 | | 163-5x=5x+13 | | 4.5z-7.2=6.3 | | 14T=56 | | -4u-15=0 | | y=30(0.92) | | 0.7t-8.3=-2 | | -2x-16=0 | | 0=5u-16 | | 6W=18 | | 0=8u+5 | | 7x-14=5x+6 | | 8v+14=-18 | | 11x-3=7x+2 | | 3v-5=1 | | 258-6x=39x+23 | | 8(4u-1)-11u=11(2u-6) | | -5u-19=3 | | 5-9x=35-10x | | -5y-8=2 | | -8=-6z+19 |